The word and the world: A resonant textual fragment of Íslendinga saga - Úlfar Bragason (Universität Tübingen, 2004)
The paper investigates into the narratology of the Sturlunga compilation: how the events of the 12th and 13th centuries in Iceland are turn into narrative in the contemporary sagas. I will take examples of the ways of selecting and organizing the story material, and the principle of narration. I will argue that the recognition and appreciation of the narrative nature of the Sturlunga are long overdue and will show by the example of Islendinga saga by Sturla Thordarson that it is necessary to understand the narrative rules of the contemporary sagas before making use of them as sources of the history of the Sturlung Age.